Enactors or reactors? Work-life border management for women in law in Nigeria - Beauregard, T. Alexandra; Adisa, Toyin Ajibade (Community, Work and Family, 2021)
Work-family border theory casts individuals as protagonists who are enactive rather than reactive in shaping borders between work and personal life domains. To what extent is this the case in strongly patriarchal contexts that constrain women’s personal agency? This qualitative study conducted with 32 female lawyers, magistrates and justices in Nigeria shows how participants engage in new border management tactics in response to context-specific institutional and social factors. Faced with public harassment and physical assault in a country where violence against women is normalised, female legal professionals restructure family borders to extend no further than their homes and retain police attachés as border-keepers. When their families are reconfigured via nonconsensual polygamous marriages, women’s work borders are strengthened by co-wives performing domestic labour and family borders are strengthened by co-wives’ assistance with job tasks, thereby reducing participants’ work-family conflict. Rather than strategically enacting work-life borders within known situational constraints, Nigerian female legal professionals react to involuntary events that limit their agency to negotiate desired work and personal lives. © 2021 Informa UK Limited, trading as Taylor & Francis Group.
Keywords: 2000 à aujourd'hui; afrique; approches et analyses; conciliation famille-travail; famille; intersectionnalité; maternité; nigeria; patriarcat; polygamie; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; systèmes d'oppressions; thématiques; travail

Conciliation vie familiale et vie professionnelle par les femmes travaillant dans le secteur public de la santé à Lomé : quelles stratégies d’adaptation ? - Bilampoa, Gnoumou Thiombiano; Sitsopé, Toudeka Ayawavi; David, Jean Simon (Interventions Économiques, 2021)
Cet article cerne les difficultés, les défis et les stratégies mises en œuvre par les femmes soignantes à Lomé (Togo) dans la conciliation travail-famille. Les données qualitatives ont été collectées auprès de femmes soignantes dans deux formations sanitaires publiques, de leur conjoint et de leurs collègues hommes. Les résultats montrent que les normes et les pratiques culturelles ont confiné les hommes et les femmes dans leurs rôles respectifs selon la division sexuelle du travail. Ainsi, exercer des tâches domestiques est considéré comme un devoir pour les femmes, mais une transgression des normes sociales pour les hommes. Les exigences et les conditions de la profession médicale et l’insuffisance de personnels de santé rendent difficile la conciliation travail-famille pour les femmes. Pour concilier leur vie familiale et professionnelle, les femmes soignantes mettent en œuvre plusieurs stratégies d’adaptation : recours à l’aide parentale, emploi de domestiques et de répétiteurs scolaires, acquisition d’appareils électroménagers.
Keywords: 2000 à aujourd'hui; afrique; approches et analyses; care; conciliation famille-travail; famille; patriarcat; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; santé; systèmes d'oppressions; thématiques; togo; travail; travail domestique; travail du care

Paid and unpaid work during the Covid-19 pandemic: A study of the gendered division of domestic responsibilities during lockdown - Borah Hazarika, Obja; Das, Sarmistha (Journal of Gender Studies, 2021)
The Covid-19 pandemic and the strategies implemented to deal with it have had economic and societal repercussions all over the world. In India, a nationwide lockdown was initiated on 25 March 2020 which continued in a diluted form as we were conducting the interviews for the paper in July 2020. The lockdown brought activities outside the home to a standstill and people were expected to stay indoors in order to ensure social distancing and break the chain of infection. The lockdown sparked its own problems and triggered discussions on issues including economic hardship and domestic violence. The question of how domestic responsibilities are shared among adults in families has also come to the forefront of debate. As hired part-time help was discontinued under lockdown, parents who had hitherto outsourced childcare and housework were suddenly left to fend for themselves. This article attempts to explore the manner in which such unpaid domestic responsibilities, especially childcare, were shared between parents in middle-class homes. The gendered nature of this division of housework and care work, and its varied implications on the paid work and careers of mothers and fathers, is the focus of inquiry. © 2020 Informa UK Limited, trading as Taylor & Francis Group.
Keywords: 2000 à aujourd'hui; 2020-2029; asie; conciliation famille-travail; confinement; covid-19; discipline; division sexuelle du travail; famille; inde; pandémie; projet charge mentale; périodes historiques; régions géographiques; science politique; science politique et droit; soins aux enfants; thématiques; travail; travail domestique

Emotion work and gender inequality in transnational family life - Chávez, Sergio; Paige, Robin; Edelblute, Heather (Journal of Family Issues, 2021)
This study examines the emotion work of non-migrant women as they seek to sustain family life across borders. We draw on in-depth interviews with 59 non-migrant women in Guanajuato, Mexico who had immigrant spouses in the USA to assess emotion work dynamics between partners. Our analysis reveals that non-migrant women do emotion work that entails imagining lives abroad and then tailoring emotional support that addresses the needs of spouses. We also discuss how the difficulties associated with prolonged separation leads women to suppress their own needs and feelings, which can lead to emotional burnout and marital conflict. Putting non-migrant women and their activities at the center of our analysis highlights the emotional costs of migration for those who remain behind and the ways in which emotion work is a highly gendered activity that reinforces inequality through communication. We highlight how women’s subordinated status in transnational Mexican families and the need to keep the remittances flowing help explain why emotion work falls largely on women. © The Author(s) 2021.
Keywords: 2000 à aujourd'hui; amériques; discipline; famille; le coût émotionnel de la migration; mexique; projet charge mentale; périodes historiques; régions géographiques; santé; sciences humaines; sociologie; thématiques; travail; travail émotionnel

“You’re a teacher you’re a mother, you’re a worker”: Gender inequality during COVID‐19 in Ireland - Clark, Serena; McGrane, Amy; Boyle, Neasa; Joksimovic, Natasha; Burke, Lydia; Rock, Nicole; Katriona O’ Sullivan (Gender, Work and Organization, 2021)
The novel coronavirus (COVID‐19) was declared a global pandemic in March 2020. Unlike previous highly contagious diseases that brought the threat of global instability this century such as SARS‐CoV, Zika virus (ZIKV), Swine flu (H1N1), and the Avian flu (H5N1), COVID‐19 was unable to be contained. Global restrictions were implemented to curb the spread of the virus, which included but were not limited to the closure of all educational institutions and the advice to engage in remote working. This study aims to understand the experience of working mothers who managed work and home duties during the COVID‐19 pandemic in Ireland. Thirty working mothers were interviewed in this study, and qualitative analyses were conducted to gain insight into their work and family life during the restrictions. The findings of the analysis indicate that working mothers have been negatively impacted by COVID‐19 in relation to their psychological well‐being, experiences of negative emotions, and the redefinition of family dynamics, in which working mothers have adopted additional and disproportionate care burden. These findings are consistent with the current research arguing that COVID‐19 has highlighted an increase in the gender gap in domestic labor as well as the undermining of career advancement for working mothers.
Keywords: approches et analyses; charge mentale; conciliation famille-travail; division sexuelle du travail; europe; famille; irelande; projet charge mentale; rapports sociaux de sexe; régions géographiques; santé; soins aux enfants; thématiques; travail; travail domestique

« La propriété d’une maison pavillonnaire dans l’imaginaire de la famille et les conditions économiques des familles avec enfants » dans Des imaginaires aux réalités conjugales et familiales: perspectives interdisciplinaires et internationales - Pugliese, Maude (Des imaginaires aux réalités conjugales et familiales: perspectives interdisciplinaires et internationales, 2021)
"La réalisation des projets de couple et familiaux constitue des préoccupations importantes des individus contemporains. Ces projets font l'objet de représentations sociales générées par diverses sources?: œuvres littéraires, philosophiques, scientifiques, populaires, mais aussi cinématographiques ou médiatiques. Ces représentations proposent des modèles et fournissent des supports à des imaginaires alimentant les scénarios personnels, créant des attentes qui se heurtent aux réalités quotidiennes, et qui entrainent souvent des désillusions et des déceptions, mais aussi des adaptations. Dans le but de mieux saisir les logiques à l'œuvre dans les attentes conjugales et familiales, cet ouvrage composé de treize chapitres rédigés par des chercheuses et chercheurs québécois, canadiens et internationaux (Brésil, Espagne, France, Suisse), issus de disciplines variées (anthropologie, démographie, psychologie, sexologie, sociologie et travail social), vise à mettre en évidence l'influence des imaginaires sur les itinéraires conjugaux et familiaux. La richesse des contributions à cet ouvrage collectif devrait aider à mieux saisir l'importance des études sur les imaginaires familiaux, autant pour la communauté scientifique que pour toute personne intéressée à mieux comprendre, et possiblement à mieux accompagner, les imaginaires, les attentes et les désillusions conjugales et familiales vécues par les individus et les couples."
Keywords: 2000 à aujourd'hui; 2010-2019; amérique du nord; amériques; approches et analyses; canada; care; cours; discipline; europe; famille; inégalités; maternité; patriarcat; premier cycle; périodes historiques; régions géographiques; sciences humaines; soc2264; sociologie; systèmes d'oppressions; thématiques

Undocumented mothers and work–family conflict in restrictive policy contexts - Straut-Eppsteiner, Holly (Journal of Marriage and Family, 2021)
Objectif Cette recherche examine la manière dont les mères latines sans papiers négocient le conflit travail-famille dans un contexte de politiques d’immigration restrictives. Arrière-plan Aux États-Unis, les femmes continuent de lutter contre les tensions entre travail et famille, et les femmes pauvres sont confrontées à des contraintes particulières. Les immigrées latinos se sont de plus en plus installées et ont fondé des familles aux États-Unis, et ont rejoint le marché du travail dans des emplois à bas salaires. Contrairement aux femmes nées aux États-Unis, ces femmes doivent faire face à des politiques d’immigration restrictives, ce qui suggère de nouveaux domaines de compréhension des inégalités intersectionnelles qui façonnent le conflit travail-famille. Méthode Les résultats sont basés sur des entretiens approfondis menés auprès de 45 mères immigrantes latinos en Caroline du Nord qui avaient une expérience du marché du travail rémunéré. Les sujets d'entretien comprenaient la famille, le travail et la migration tout au long de la vie des femmes. Résultats Les contextes politiques spécifiques au lieu, les conditions de travail, les attentes patriarcales et le manque d'accès aux réseaux de soins remettent en question la capacité des immigrantes latines à remplir le double rôle de mère qu'elles occupent à la fois en tant que pourvoyeuses de famille et en tant que soignantes et nourricières de leurs enfants. Conclusion Les attentes sociales liées à la maternité ajoutent une dimension de précarité au statut vulnérable des femmes en tant que travailleuses sans papiers et démontrent l’impact genré des politiques d’immigration. Conséquences Les politiques restrictives rendent de plus en plus difficile pour les femmes sans papiers d’obtenir ou de changer d’emploi sur le marché du travail à bas salaires. Les résultats soulignent l’importance de prendre en compte le statut d’immigrant dans les études sur les conflits travail-famille, en particulier à l’heure où les politiques ciblant les immigrés s’intensifient.
Keywords: amériques; approches et analyses; conciliation famille-travail; famille; femmes latino-américaines; femmes migrantes*; inégalités; patriarcat; politiques migratoires; projet charge mentale; racisme; régions géographiques; santé; santé mentale; sexisme; systèmes d'oppressions; thématiques; travail; travail reproductif; états-unis